Efficient Access to All‐Carbon Quaternary and Tertiary α‐Functionalized Homoallyl‐type Aldehydes from Ketones. (1st September 2017) - Pace, Vittorio; Castoldi, Laura; Mazzeo, Eugenia; Rui, Marta; Langer, Thierry; Holzer, Wolfgang
Abstract: β, γ‐Unsaturated aldehydes with all‐carbon quaternary or tertiary α‐centers were rapidly assembled from ketones through a unique synthetic operation consisting of 1) C1 homologation, 2) Lewis acid mediated epoxide–aldehyde isomerization, and 3) electrophilic trapping. The synthetic equivalence of a vinyl oxirane and a β, γ‐unsaturated aldehyde is the key concept of this previously undisclosed tactic. Mechanistic studies and labeling experiments suggest that an aldehyde enolate is a crucial intermediate. The homologating carbenoid formation plays a critical role in determining the chemoselectivity. Abstract : β, γ‐Ungesättigte Aldehyde mit quartären oder tertiären α‐Positionen wurden ausgehend von Ketonen durch eine neue Reaktionssequenz aus C1 ‐Homologisierung, Lewis‐Säure‐vermittelter Epoxid‐Aldehyd‐Isomerisierung und elektrophilem Abfangen erhalten. Mechanistische Studien und Markierungsexperimente deuten auf ein Aldehydenolat als wichtiges Reaktionsintermediat.